The Impact of Corruption on the Effectiveness of Public Administration in Nigeria - Omololu Adex Bamigboye; Isaiah Omotayo Fakunle (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2025)
Corruption remains a persistent structural challenge undermining governance quality and public sector performance in Nigeria. Despite the establishment of multiple anti-corruption institutions and legislative reforms, public administration effectiveness continues to be compromised, raising concerns about institutional capacity and accountability. This study examines the impact of corruption on the effectiveness of public administration in Nigeria. The study adopts a structured narrative literature review methodology, drawing on peer-reviewed articles, policy documents, and institutional reports published between 1990 and 2025. Using qualitative content analysis, the study synthesizes existing evidence to identify dominant forms of corruption and their institutional consequences. The findings reveal that corruption distorts policy implementation, weakens accountability mechanisms, erodes public trust, reduces service delivery efficiency, and entrenches administrative dysfunction. The study concludes that sustainable improvement in public administration effectiveness requires strengthening institutional independence, enhancing transparency frameworks, digitizing public sector processes, improving public servant welfare structures, and enforcing accountability mechanisms. These findings contribute to the governance reform discourse by providing an integrated analytical framework linking corruption dynamics to administrative performance outcomes in Nigeria.